"Are you crewed up with that bird from the uni?" the complexities of conducting ethnographic research in policing. Issue 3 (13th October 2020) - Cox, Claudia Emeline
Abstract : Purpose: The purpose of this paper is to provide some initial reflections on the complexities and challenges faced when conducting observations with police officers working in response and neighbourhood policing roles from the perspective of a young, female, researcher. Design/methodology/approach: The research consisted of 200 hours spent with operational police officers in a medium sized UK police force, predominantly in 3 cities, to explore the realities of frontline policing and policy implementation. This paper offers a reflexive account of conducting the research, as opposed to a discussion of the findings which align to the original research aim. Findings: Conducting this fieldwork highlighted a number of complexities arising as a result of conducting ethnographic research in policing. This paper is concerned with the constructing of a researcher identity and navigating moral dilemmas based on the culture and use of language observed. Originality/value: Whilst this will be of interest to those engaged with similar policing research, such findings are also likely to apply to those conducting ethnography where there is conflict between their insider/outsider status, the potential for internalised moral debates and women conducting research in male-dominated settings.